The ubiquitin ligase c-CBL is expressed in undifferentiated marmoset monkey pluripotent stem cells but is not a general stem cell marker - Rodriguez-Polo, Ignacio (Primate Biol, 2017)
The protein c-CBL is a ubiquitin ligase. It catalyzes the last step of the transfer of ubiquitin to target proteins. Upon completion of polyubiquitination, the target proteins are degraded. Clinically, it is important that c-CBL is mutated in a subset of patients who develop myeloid malignancies, which are diseases of the hematopoietic stem or progenitor cells. c-CBL has also been shown to be expressed by human spermatogonia. The whole spermatogonial cell population possesses a subset that comprises also the spermatogonial stem cells. Based on these findings we hypothesized that c-CBL might be a general stem cell marker. To test this, we first validated the antibody using marmoset bone marrow and adult testis. In both tissues, the expected staining pattern was observed. Western blot analysis revealed only one band of the expected size. Then, we examined the expression of c-CBL in marmoset monkey embryonic stem (ES) cells, induced pluripotent stem (iPS) cells and adult stem cells. We found that c-CBL is strongly expressed in undifferentiated marmoset iPS cells and ES cells. However, adult stem cells in the gut and the stomach did not express c-CBL, indicating that c-CBL is not a general stem cell marker. In summary, c-CBL is strongly expressed in pluripotent stem cells of the marmoset monkey as well as in selected adult stem cell types. Future studies will define the function of c-CBL in pluripotent stem cells.